Figure 6 from Predicting Molecular Subtype and Survival of Rhabdomyosarcoma Patients Using Deep Learning of H&E Images: A Report from the Children's Oncology Group - David Milewski (15050643) (2025)
Deep learning algorithms can predict event-free and overall survival from H&E histology alone. A, Schematic for training a convolutional neural network for survival. Patients with FN-RMS (n = 264) were partitioned into three groups based on EFS length to ensure even sampling and fed into a deep learning architecture with a Cox proportional hazard layer to assess risk. B, Kaplan–Meier curves for EFS based on COG clinical risk group assessment. C, Kaplan–Meier curves for event-free survival based on A.I. hazard prediction. D, Kaplan–Meier curves for OS based on COG clinical risk group assessment. E, Kaplan–Meier curves for OS based on the same A.I.-predicted risk grouping as in C.